Improved mechanical and moisture-resistant properties of woven hybrid epoxy composites by graphene nanoplatelets (GNP) - Naveen, Jesuarockiam; Jawaid, Mohammad; Zainudin, Edi Syams; Hameed Sultan, Mohamed Thariq; Yahaya, Ridwan (MDPI, 2019)
This research investigated the effect of adding different wt.% (0, 0.25, 0.50, and 0.75) of GNP (graphene nanoplatelets) to improve the mechanical and moisture resistant properties of Kevlar (K)/cocos nucifera sheath (CS)/epoxy hybrid composites. The laminates were fabricated with different K/CS weight ratios such as 100/0 (S1), 75/25 (S2), 50/50 (S3), 25/75 (S4), and 0/100 (S5). The results revealed that the addition of GNP improved the tensile, flexural, and impact properties of laminated composites. However, the optimal wt.% of GNP varies with different laminates. A moisture diffusion analysis showed that the laminates with a 0.25 wt.% of GNP content efficiently hindered water uptake by closing all the unoccupied pores inside the laminate. Morphological investigations (SEM and FE-SEM (Field Emission Scanning Electron Microscope)) proved that the addition of GNP improved the interfacial adhesion and dispersion. Structural (XRD and FTIR) analyses reveals that at 0.25 wt.% of GNP, all the hybrid composites showed a better crystallinity index and the functional groups presents in the GNP can form strong interactions with the fibers and matrix. A statistical analysis was performed using One-way ANOVA, and it corroborates that the mechanical properties of different laminates showed a statistically significant difference. Hence, these GNP-modified epoxy hybrid composites can be efficiently utilized in load-bearing structures.